The genus Helionothrips (Thysanoptera, Panchaetothripinae) in China, with two new species and an identification key - Xie, Yanlan; Li, Yajin; Zhang, Hongrui (Zootaxa, 2022)
With 28 listed species Helionothrips Bagnall is the most species-rich genus within the subfamily Panchaetothripinae. Problems are discussed with several character states used for species discrimination: fore wing color; thoracic sculpture; sense cone length on antennal segment IV; male sternal pore plates. An identification key is provided to 15 species of Helionothrips known in China, including H. pallidus sp. n. and H. phragmitesi sp.n. from Southwestern China.